Conjugate forced convection transient flow and heat transfer analysis in a hexagonal, partitioned, air filled cavity with dynamic modulator. (March 2021) - Ikram, Maruf Md.; Saha, Goutam; Saha, Suvash C.
Abstract: Background: – Forced convection heat transfer in a cavity is of great importance due to its strong relevance to the practical aspects. Most of the studies focus on this topic from a steady perspective. But adding a flow modulator enhances a system's thermodynamic performance and makes such a system more realistic and widens the field of application. Such studies are unsteady and often quite expensive. As a result, only a few literatures are available with very idealistic geometric configuration and boundary conditions. Methodology: – Two-dimensional unsteady continuity, momentum and energy equations are used for the mathematical modeling of the problem incorporating the Boussinesq approximation. A free triangular discretization scheme is adopted to solve the moving mesh problem by formulating the Arbitrary Lagrangian Euler (ALE) finite element approach. Parameters: – Numerical studies are carried out for a fixed Prandtl number ( Pr = 0.71) and fixed geometry of the rotating blade while varying the other parameters i.e. Rayleigh number, Reynolds number and Biot number. This dynamic boundary problem encompasses a wide range of parameters i.e. (100 ≤ Re ≤ 10 3 ), (10 3 ≤ Bi ≤ 10 4 ) and (10 4 ≤ Ra ≤ 10 7 ) to evaluate the thermodynamic behavior of the thermo-fluid system. External flow condition is taken into consideration in terms of Biot number. Effects of these parameters are visualized through streamlines, heatlines, spatially average Nusselt number evaluated on the heated surface and system effectiveness. Objective: – Present computational study focuses on the transient analysis of the conjugate forced convection flow and heat transfer characteristics in a hexagonal, air filled cavity. This cavity is equipped with a floor heater of constant heat flux under the rotational influence of an adiabatic flow modulator. And the blade is placed in the central position of the cavity which is rotating in the clockwise direction. Also, the whole computational domain is composed of four different domains, one convective domain and three solid domains. The solid domains are made of brick and glass as per their practical aspects. Findings: – A Fast Fourier Transform (FFT) analysis is presented to comprehend the thermo-oscillating system response. FFT plots indicate that for all of the cases the fundamental frequency of the system response conforms to the blade frequency. Moreover, present numerical results show that the heat transfer effectiveness has an inverse relationship with the Biot and Rayleigh numbers while improves significantly with the increase of Reynolds number and reaches a critical state for Recr = 650. Higher Reynolds number also attenuates the degree of power spectrum. Conclusion: – To attain a higher heat transfer effectiveness the thermo – fluid system should be operated at low Rayleigh number with higher Reynolds number.